Analysis of the Influence of Competency on Employee Performance at the Percut Sei Tuan Sub-district Office, Deli Serdang Regency - Arynaldi Harahap; Wahyu Kristian Hutodo Napitupulu; M. Yogie Adlin; Adi Saputra Sirait; Gebriel Vincentsius Siregar (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of competence on employee performance at the Percut Sei Tuan Subdistrict Office, Deli Serdang Regency. This research uses a quantitative approach with an associative research method. The population in this study consisted of all employees working at the Percut Sei Tuan Subdistrict Office, with a total of 42 respondents. Data collection techniques were conducted through questionnaires, observation, and documentation. The collected data were analyzed using simple linear regression analysis with statistical testing. The results of the study indicate that competence has a significant effect on employee performance. This is evidenced by the results of the t-test which show that the calculated t value of 2.770 is greater than the t-table value of 2.023 at a significance level of 5%. These results indicate that the better the competence possessed by employees, the higher the level of performance produced. Competence which includes knowledge, skills, and work attitudes can improve the effectiveness of employees in carrying out their duties and responsibilities. Therefore, improving employee competence through training and human resource development needs to be continuously implemented to enhance employee performance and the quality of public services at the Percut Sei Tuan Subdistrict Office, Deli Serdang Regency.